The effects of geometrical flame feature on radiant heat flux prediction of horizontal jet flames using line source model. (26th February 2022) - Ab Aziz, Nur Shahidah; Md. Kasmani, Rafiziana
Abstract: Radiant heat flux and impingement are the most common contributors to accident escalation involving jet fire. Thus, it is important to account for the radiant heat flux by using a semi‐empirical model as it is easy, cheaper, and could provide a reliable prediction. In this study, experimental observations were carried out for both free and impinging jet release. Propane was used as fuel and released from a circular nozzle with a diameter of 7.15 and 9.8 mm. The release velocity was fixed between 27 to 65 m/s, which is considered a subsonic release. In this work, two bases for radiant heat prediction using LSM were used: (i) horizontal kite shape approach and (ii) flame trajectory approach. It was observed that the prediction of radiant heat flux based on the flame trajectory for the free jet fire scenario gave the R 2 value of 0.99, suggesting that the flame trajectory could give a better prediction as compared to the horizontal kite shape approach with R 2 = 0.94. By using a similar assumption for impinging jet flames, it was observed that LSM based on flame trajectory could be used to predict the radiant heat flux with R 2 = 0.99 for each case scenario.